Emerging Pediatric HIV Epidemic Related to Migration - Douglas W. MacPherson; Militza Zencovich; Brian D. Gushulak (Emerging Infectious Diseases, 2006)
In 2002, Canada introduced routine, mandatory HIV antibody screening for all residency applicants, including selected children. We report screening results from January 2002 to February 2005. Thirty-six pediatric HIV cases were detected (14/100,000 applicants); 94% of infected children were eligible to arrive in Canada. Thirty-two of the affected children were from Africa, and maternal infection was the main risk factor. Only 4 (11%) of the children had received antiretroviral therapy. In countries of low HIV incidence, migration-related imported infection in children may be an emerging epidemic. The early identification of HIV-infected immigrant women permits intervention to prevent mother-to-child HIV transmission. Routine HIV testing as a component of the medical examination of immigrants has national and international health policy and programmatic implications.